Formação continuada de gestores pedagógicos com a Obutchénie por Unidades: análise na perspectiva de L.I. Bozhovich - Jesús, Sônia Ferreira de (2022)
The study addresses the continuing developmental training of pedagogical managers – school supervisors, coordinators and pedagogical deputy directors – from the perspective of Historical-Cultural Theory (HCT), focusing on the constitution of their affective and motivational spheres. The training dimension of the work of these professionals was considered, as they are subjects that systematize training processes in formal education contexts. After surveying and concluding that the training of pedagogical managers has gaps in terms of integral and systemic learning, in the sense of encompassing the affective and motivational spheres in training activities, considering the affect-cognition unit, the following questions were established: how should a training process with pedagogical managers be systematized, so that it culminates in the integral and systemic development of these professionals, in the view of their affective spheres and motivations and when considering the Bozhovichian approach? Is it possible to say that the development of their personality, by paying attention to the driving forces that develop themselves, allows them to continue with the school staff, guided by imitative and creative movements under the same conditions? Within the scope of Historical-Dialectical Materialism (HDM), HCT and Developmental Didactics (DD) and based on the theoretical assumptions of L.I. Bozhovich, Study Activity Theory and Obutchenie by Units, the objective was to analyze the development of affective spheres and motivations of the pedagogical manager in a continuous training process. To this end, training research was systematized characterized by aspects of didactic-training intervention and research by groups, whose demand led to training activities with professionals remotely, due to the pandemic period of coronavirus disease (the new coronavirus disease – COVID-19), which consisted of synchronous (Moodle Platform) and asynchronous (webconference) activities. Data analysis made use of laws, categories and principles of the MHC and the methodology of episodes and scenes. The assumption that guided the theoretical, epistemological and methodological study was that the affective and motivational spheres of the pedagogical managers need to be considered in the organization of training processes; the aspects inherent to it have a dynamic that guides the personality. Therefore, one should not envisage, as primary parameters, the object, material or immaterial forms in the regulation of behavior, but the self-regulating and self-generating nature of the psyche. If studies through the formation of scientific concepts develop theoretical thinking, it was inferred that cognitive sphere is not formed apart from the scope of emotions and motivations, with the respective defense of systemic development of the pedagogical manager. Of The analyzes raised syntheses that the training process for pedagogical managers needs to follow some principles and use constitutive units, with a view to the systemic development: the training-work unit, which implies considering training activities in connection with work demands; and the content-form unit, revisited from the perspective of affective and volitional aspects. Consequently, it was emphasized that development of affective and mediated needs is constituted through the movement directed by such units; and according to the principles, it was indicated that affective and motivational spheres develop themselves due to the configurations outlined by the subjects’ movements in the training activities. In the meantime, feelings with different essences emerged, as well as intentions were formed as driving forces of conduct, in addition to the position occupied by professionals demonstrating the themes to be addressed in the training movement. Furthermore, it is necessary to develop the systemic view of trainers of the trainer on the processes, to understand the systemic development practices of training and to this factor reverberates in praxis.